Can Code Switching Indicate Personal Branding?: A Case Study of Higher Education Students in Indonesia - Rahmah, Mila Afidah; Indhiarti, Tantri Refa (Journal of English Language Teaching and Linguistics, 2021)
The goal of this research is to have a better understanding of how students can grow into their own personal brands by switching their languages. The study takes a qualitative approach, and the data were gathered through interviews via Google Forms. The interviewees were all current Brawijaya University students from departments of English Education and English Literature. There are fifty students telling their experiences while comitting code switching and how they obtained the stereotype. According to the findings, the primary goal of developing a personal brand is to gain confidence, where a personal brand will help them stand out among their competitors. It is also discovered that code switching and personal branding are not yet being practiced to the extent that it could be due to the limited research in this area previously. However, we have discovered that people are interested in this phenomenon because it is more a matter of individuals' lack of knowledge about personal branding that is limiting them.